Al-Hamz and Al-Tas‘heel in Maqamat al-Hariri explanation - Abdel, Zaidoun Fadel; Al Daraji, Hadeel Raad Tahseen (Journal of Humanities & Social Sciences, 2017)
It is a study of the audio mabahith in the book "sharh muqammad bin Othman al_hariri al_basri and we found the phenomenon of hamz and its facilitation on a large part of the importance worthy of research and study and after completing the collection of the research material its nature required to be divided into two sections and sealed with the conclusion of the results of the search and than followed by the list of sources and references which we benefited from in our study and this was many and varied dealt with in the first section:the phenomenon of facilitating hamza included the facilitation of hamza between wabdal hamza in the letters of the thousand and the Wawa p hamza and allocated the second section:to achieve hamzah and we conclusion showing the results of the research.